(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In terms of the rising environmental awareness importance our main research question was if national economies in EU member states have any effect on the number of ISO 14001-certified organizations. Purpose: The primary purpose of the research was to obtain the answer to our research problem of whether national economies in EU member states affect the number of organizations that have the certified ISO 14001 environmental management system in place and to explore the trend of the number of certificates in the European Union. Method: An empirical analysis was conducted using the data of ISO, the International Organization for Standardization, on the number of ISO 14001 certificates in 2019, and the data of Eurostat for selected national macroeconomic indicators. Our research included a survey of 28 EU member states in 2019. The distribution of data is shown by bar charts. Statistical processing of numerical data used in the analysis was done by means of the Minitab software. Prior to statistical processing, non-normally distributed data was transformed with the Johnson transformation method. The hypotheses were verified on the basis of the calculated Pearson correlation coefficients »r« between the examined factors. Results: In 2019, there were 92,290 organizations in EU member states that held the ISO 14001 certificate. In absolute numbers of certificates, the top five countries are the so-called »older EU member states«, namely Italy, Spain, the United Kingdom, Germany and France. The highest number of certificates per one billion EUR of GDP was identified in the so-called »new member states«, namely Bulgaria, Croatia, Romania, the Czech Republic and Estonia. The main finding of our research is that the level of GDP affects the number of ISO 14001 certificates in EU member states since, according to the calculated Pearson correlation coefficient, there is a strong correlation between the two studied factors. Other examined national macroeconomic factors, such as general government expenditure for environmental protection, environmental tax revenues and global competitiveness index rating, have no effect on the number of ISO 14001 certificates. Organization: The research provides organizations with an overview of the current situation regarding the number of ISO 14001 certificates in EU member states. The shown positive trend in the growth of the number of certificates can be an additional motivation factor for those organizations that have yet to decide on certification. Society: The finding that the certified ISO 14001 environmental management system is a useful and effective management tool is important both for organizations as well as wider society because it brings enhanced environmental performance and sustainability, competitive advantage as well as financial and organizational performance. Originality: Considering that our research included all 28 EU member states in 2019 and the fact that the latest publicly available data on the number of ISO 14001 certificates in 2019 was used, it is our belief that our research is unique from this point of view. Limitations / further research: The research was narrowed down to 28 EU member states. The hypotheses were verified on the basis of the latest publicly available data for year 2019 published by ISO. It would make sense to continue our research and, in addition to our four discussed factors, to examine other national macroeconomic indicators. Thus, it would be possible to establish whether there are other factors, in addition to GDP, that have a positive impact on the growth of the number of ISO 14001 certificates. Moreover, the research could also include other countries on the European continent that are not necessarily EU member states.